Social and Institutional Capability for the Management of Agro-Biodiversity: Evaluation on an International Case Study - Patera, Salvatore (Revista del CLAD Reforma y Democracia, 2016)
The problems connected to conventional agriculture promoted by some multinationals find fruitful ground in international agreements mainly oriented to the patenting of seeds, local knowledge and traditional processes/products. Thus, few varieties are favoured compared to the detriment of the biodiversity that communities own as cultivation and culture. Since the objectives of KHFA (Knowledge, Health and Food for All) project, it’s observed that an alternative model of management of agro-biodiversity should contain a combined use both of regulatory and legal tools and of socio-educational device for ensuring local communities to safeguard and value their local knowledge, skills and traditional knowledge in a framework of self/co-management of these common goods at one with institutions.This article shows the results of KHFA project, with reference to normative- legal tools developed in deliberative focus groups by numerous international experts and professionals get involved in the project. These deliberative focus groups have successfully produced a Concerted Document carrying out some specific proposals aimed at promoting agro-biodiversity along a dialogue between communities and institutions. These proposals, developed in the advocay and lobbying campaigns of the project were summerized in a motion. The Committee of the Regions of Europe submitted this motion for ratification by some local, regional and national governments also pushing for its implementation. At the end of the project, an expert group has assessed the project using the technique of scale of priorities.
Keywords: Agriculture; Community Development; Rural Community; Protection of Rights; International Context; Europe